PEMIKIRAN KH. HASYIM ASY’ARI TENTANG ISLAM DAN KEBANGSAAN DALAM PERSPEKTIF NASIONALISME RELIGIUS DI INDONESIA - M. Anang Sholikhudin; Ainul Fidia; Nuril Laila (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
This article explores KH. Hasyim Asy'ari's thoughts on the relationship between Islam and nationality from the perspective of Indonesian religious nationalism. According to KH. Hasyim Asy'ari, Islam and nationalism are not contradictory; on the contrary, they work together to build a religious and nationalistic nation. The concept of “Hubbul Wathan Minal Iman,” which means “love of the homeland is part of faith,” serves as a moral and spiritual foundation that combines the spirit of nationalism with the faith of Muslims. He demonstrated strong and inclusive Islamic nationalism in his struggle for independence, particularly through the Jihad Resolution fatwa and the establishment of Nahdlatul Ulama. This religious nationalism is still applied in education, religious moderation, and strengthening national unity today. Building a moderate, tolerant, and socially just national character is based on the thinking of KH. Hasyim Asy'ari. The results of the study show that the intellectual and practical legacy of KH. Hasyim Asy'ari has contributed significantly to the formation of a harmonious Indonesian national identity based on Islamic values.